Strategic Choice of Network Externality - Yuanzhu Lu; Sougata Poddar (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2015)
In many product markets, impact of network externality plays an important role to affect the overall quality of a product. However, the degree or the strength of network externality is assumed as a parameter in most of the literature. We propose a model of vertical product differentiation with two competing firms where the strength of network externality is endogenized as a strategic choice of the high quality firm. We show how the equilibrium market structure and market coverage depend on the cost of choosing the network strength and on the relative quality difference of the competing products. We also show that the relationship between the optimal level of network externalities and the relative quality differences of the products can be monotonic or non-monotonic.
Keywords: 330; Vertical product differentiation; Network externality; Market structure; Market coverage; Investment cost